2013
DOI: 10.2754/avb201382020141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-1,3/1,6-D-glucan in diet on productivity and humoral and cellular defense mechanisms in sheep

Abstract: The aim of this study was to determine the effect of β-1,3/1,6-D-glucan, isolated from Saccharomyces cerevisiae, on indicators of milk and meat performance in sheep as well as on selected non-specific indicators of humoral and cellular defense. The experiment was carried on 26 suckling ewes divided into 2 equal groups, and their offspring (21 in each group). The ewes were administered concentrate with the addition of β-1,3/1,6-D-glucan at a dose of 3 g/kg. Indicators of milk performance and markers of humoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 13 publications
(10 reference statements)
2
27
0
Order By: Relevance
“…In other studies, lambs (Milewski, 2009;Ząbek et al, 2013) and calves (Dobicki et al, 2005) fed diets supplemented with β-glucan were also characterized by significantly higher body weights at weaning. The cited authors attributed the noted improvements in performance parameters to the prebiotic properties and immunostimulating effects of dried yeast extract which could have improved the health status of the animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other studies, lambs (Milewski, 2009;Ząbek et al, 2013) and calves (Dobicki et al, 2005) fed diets supplemented with β-glucan were also characterized by significantly higher body weights at weaning. The cited authors attributed the noted improvements in performance parameters to the prebiotic properties and immunostimulating effects of dried yeast extract which could have improved the health status of the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Milewski (2009) also noted a significant increase (P ≤ 0.01) in the percentage of lymphocytes and a tendency towards a lower percentage of neutrophils in the blood of lambs fed diet with dried yeast addition. More recent studies revealed that both dried brewer's yeast and β-1,3/1,6-D-glucan (Ząbek et al, 2013) stimulated immune responses in lambs. These authors concluded that dietary supplementation with yeast extracts improves the immune status of animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allbrahim et al (2010) observed a higher pre-ovulatory surge of estradiol in cows administered live yeast, although this supplement did not impact the size of the ovulatory ovarian folli- (Dobicki et al, 2006(Dobicki et al, , 2007. Ząbek et al (2013) demonstrated the beneficial impact of β-1,3/1,6-D-glucan on milk yield in sheep. Biolex Beta-S yeast supplement generated an increase in milk yield of 13.54 % on day 28 and 14.04 % on day 70 of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Milewski et al, 2007, andWójcik et al, 2007). These effects were combined with a beneficial impact on meat (Milewski, 2009;Milewski et al, 2007) and milk (Ząbek et al, 2013) performance.…”
Section: Introductionmentioning
confidence: 99%